Epicene Agreement and Inflected Infinitives When the Data Is "Under Control": A Reply to Modesto (2010). (30th April 2013) - Rodrigues, Cilene; Hornstein, Norbert
Abstract: Two empirical domains in Brazilian Portuguese have recently been claimed by Modesto (2010) to be problematic for the movement theory of control. We employ experimental‐syntax methods and find that more rigorous methodology reveals a more robust set of results that undermines both lines of argumentation. The first argument concerns agreement with epicene nouns in Romance that can be used as a diagnostic for the underlying presence of a moved element and, in particular, whether embedded null subjects are the result of finite control (as movement). The evidence confirms that embedded null subjects in finite CPs pattern together with obligatory control in Brazilian Portuguese, but not in Italian, and that the methodology is sensitive enough to distinguish these two language types. The second set of experimental‐syntax results concern the interpretation of inflected infinitives in Portuguese and demonstrate that null subjects of inflected infinitives do not favor partial‐control readings, instead patterning together with nonobligatory control. As such, although they raise interesting questions about the status of pro in partial pro ‐drop grammars, inflected infinitives are orthogonal to the predictions of the movement theory of control.